STRATEGI GURU KELAS DALAM MENGATASI KESULITAN MEMBACA PADA SISWA KELAS V SD NEGERI SEJATI - Fatah Zahrasiwi, Reiki; Purnomo, Heru (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
Reading ability is one of the basic skills that is very important for elementary school students, because it is the main foundation in understanding various subjects. However, not all students are able to master this skill optimally, so that various reading difficulties arise that can hinder their academic development. This study aims to describe the strategies applied by teachers in overcoming reading difficulties in grade V students at SD Negeri Sejati. This study uses a qualitative approach with a descriptive method, which allows researchers to explore in depth the phenomena that occur naturally and contextually. The subject of the study was the grade V teacher, Mrs. Hariyani Diyati who was selected purposively. Data were collected through in-depth interviews and direct observation of classroom learning activities. The results of the study showed that teachers applied various strategies such as individual learning, the use of visual media, and approaches based on active student involvement to improve reading skills. These strategies are adjusted to the characteristics and individual needs of students who experience reading difficulties. The conclusion of this study shows that the application of adaptive and communicative learning strategies by teachers can help reduce reading difficulties and encourage significant improvements in students' literacy skills.